2021
DOI: 10.1136/rmdopen-2021-001578
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study of PF-06410293, an adalimumab (ADL) biosimilar, compared with reference ADL for the treatment of active rheumatoid arthritis: results from weeks 26–52, including a treatment switch from reference ADL to PF-06410293

Abstract: ObjectiveTo investigate the efficacy, safety, immunogenicity and pharmacokinetics of biosimilar adalimumab (ADL) PF-06410293 (ADL-PF; adalimumab-afzb) versus EU-sourced reference ADL (ADL-EU) in patients with active rheumatoid arthritis (RA) on longer-term treatment and after being switched from ADL-EU to ADL-PF.MethodsIn this multinational, double-blind study, patients with active RA were initially randomised to ADL-PF or ADL-EU for 26 weeks (treatment period (TP) 1). At the start of TP2 (weeks 26–52), patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(56 citation statements)
references
References 15 publications
3
52
0
1
Order By: Relevance
“…25 T A B L E 2 Clinical safety results in the studies finally included in the systematic review Fleischmann et al reported no clinically meaningful differences between RA treatment groups in the incidences of reported TEAEs of special interest, including injection-site reactions, anaphylaxis/ angioedema/urticaria or opportunistic infections. 26 Furst et al reported safety findings in RA patients that were consistent with the known safety profile of reference adalimumab. Most TEAEs were grade 1-2 in intensity.…”
Section: Safety Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…25 T A B L E 2 Clinical safety results in the studies finally included in the systematic review Fleischmann et al reported no clinically meaningful differences between RA treatment groups in the incidences of reported TEAEs of special interest, including injection-site reactions, anaphylaxis/ angioedema/urticaria or opportunistic infections. 26 Furst et al reported safety findings in RA patients that were consistent with the known safety profile of reference adalimumab. Most TEAEs were grade 1-2 in intensity.…”
Section: Safety Resultsmentioning
confidence: 59%
“…Eighteen of the 21 articles studied the safety of the study population (Table 2). 11,12,[20][21][22][23][24][25][26][27][28][30][31][32][34][35][36]38 Overall, infection was the most often reported treatment emergent adverse event (TEAE).…”
Section: Safety Resultsmentioning
confidence: 99%
See 3 more Smart Citations